Delayed recovery of leg fatigue symptoms following a maximal exercise session in people with multiple sclerosis. - Dawes, H; Collett, J; Meaney, A; Duda, J; Sackley, C; Wade, D; Barker, K; Izadi, H (2014)
BACKGROUND: Fatigue is a chronic symptom for people with multiple sclerosis (PwMS). OBJECTIVE: Symptoms of fatigue were investigated during and following a single exercise session. METHODS: In all, 58 PwMS and 15 healthy, low-active controls performed a cycle ergometer incremental exercise test to voluntary exhaustion. Physiological intensity (expired air and heart rate), perceived breathlessness, and leg fatigue (Rating of Perceived Exertion [RPE] CR-10 Scale) were measured during and for 10 minutes following exercise. MEASURES: of baseline disability (Barthel Index), activity (Physical Activity Scale for the Elderly), vitality (Subjective Vitality Scale), and general fatigue (Fatigue Severity Scale [FSS]) were recorded. RESULTS: PwMS had reduced exercise capacity (P = .00 to .01), but sensations of breathlessness and leg fatigue were the same at voluntary exercise termination in both groups (P = .09). PwMS with fatigue (FSS ≥ 4) exhibited reduced exercise capacity (P = .03 to .05) but reached the same physiological intensity, breathlessness, and leg fatigue symptoms at test termination as nonfatigued peers (P = .16 to .59). During recovery, there was no difference in observed means between groups, except for leg RPE, which was higher in the MS group (P = .047) and higher at 3 and 5 minutes after exercise in the fatigued MS group (P = .02). Physiological markers and breathlessness recovered at the same rate in both groups (P = .33 to .67). CONCLUSION: Monitoring leg fatigue symptoms during and through recovery from physical activities may help guide participation in physical activities for PwMS, particularly in people managing high levels of fatigue.